Unilateral pulmonary artery agenesis diagnosed in adulthood: a case report - Veena Charishma R. P.; Vinod, Sushmita; Gangadharan Vadivelu; Anbumaran P. Mani (International Journal of Advances in Medicine, 2023)
Isolated pulmonary artery agenesis (UPAA) diagnosed in adulthood is a rare congenital anomaly. It occurs during embryological development where there is a fusion failure between sixth aortic arch and pulmonary truck of affected side. Here we report a case of an adult patient with isolated unilateral right pulmonary artery aplasia.